2018
DOI: 10.1111/bjep.12240
|View full text |Cite
|
Sign up to set email alerts
|

Mind wandering, together with test anxiety and self‐efficacy, predicts student's academic self‐concept but not reading comprehension skills

Abstract: This study highlights the importance of evaluating the effects of MW on academic self-concept, taking into account a complex pattern of motivational and emotional variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 94 publications
(119 reference statements)
2
14
0
Order By: Relevance
“…Therefore, results allow suggesting that MW as a dispositional trait might not be influenced by a reading disorder, whereas children with dyslexia might be more prone to MW during self-paced reading, possibly due to disfluency, weaknesses in working memory or to a higher perceived text difficulty. The tendency to mind-wander seems more related to emotional traits, as evidenced in previous literature (Desideri et al, 2019;Seli et al, 2019) and from correlation analyses in the present study. Indeed, in the present study, only MW dispositional measures but not probes were related to anxiety and depression (Desideri et al, 2019;Seli et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, results allow suggesting that MW as a dispositional trait might not be influenced by a reading disorder, whereas children with dyslexia might be more prone to MW during self-paced reading, possibly due to disfluency, weaknesses in working memory or to a higher perceived text difficulty. The tendency to mind-wander seems more related to emotional traits, as evidenced in previous literature (Desideri et al, 2019;Seli et al, 2019) and from correlation analyses in the present study. Indeed, in the present study, only MW dispositional measures but not probes were related to anxiety and depression (Desideri et al, 2019;Seli et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…The tendency to mind-wander seems more related to emotional traits, as evidenced in previous literature (Desideri et al, 2019;Seli et al, 2019) and from correlation analyses in the present study. Indeed, in the present study, only MW dispositional measures but not probes were related to anxiety and depression (Desideri et al, 2019;Seli et al, 2019). Therefore, it might be hypothesized that mood disorders might detract additional resources from working memory, leading to having one's mind engaged in negative thoughts during cognitive tasks.…”
Section: Discussionsupporting
confidence: 87%
“…At times, mind-wandering may occur consciously as an evolutionary human mechanism to evade boredom or lower cognitive fatigue; however, mind-wandering may also occur unconsciously [50] . On one hand, task-related mind-wandering, where a person starts with some thoughts related to a task and mind wanders, has been shown to exhibit benefits such as creativity and future planning [31 , 71] . On the other hand, task-unrelated mind-wandering, or off-task thought, is the act of mind-wandering to thoughts completely unrelated to the primary task [88 , 93] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Engagement has been found to have a significant and positive relationship with student outcomes such as students’ progress in learning, course satisfaction, and course grades (Bolliger & Halupa, 2018 ). When online courses are not grounded in learning theory, or they are difficult to navigate, uninteresting, or unengaging, studies have shown that this will likely lead to negative course engagement behaviors such as increased mind-wandering, or the directing of attention away from a primary task (Desideri et al, 2019 ). Elaboration strategies are students’ ability to store information into their long-term memory through the summative aligning of conceptual content and activities (Pintrich et al, 1993 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%